The Role of Community-based Health Services in Sexual and Reproductive Needs of Transgender People - Farnaz Farnam; Azar Nematollahi (Shiraz University of Medical Sciences, 2023)
The term transgender refers to those whose gender identity is different from their birth sex. Studiesestimate that gender-diverse persons represent 0.1-2% of populations investigated.1